Analisis Perubahan Tutupan Lahan dan Dampaknya terhadap Ketahanan Pangan di Kota Bukittinggi - Muhammad Irfansyah; Arie Yulfa (Geosfera: Jurnal Penelitian Geografi, 2025)
This study aims to: (1) analyze land-cover changes from 2018 to 2024, and (2) analyze the impact of paddy field conversion for food security in Bukittinggi City. A quantitative descriptive approach based on Geographic Information Systems (GIS) was employed, using Sentinel-2 image classification with the Random Forest algorithm. Land-use changes were analyzed through overlay techniques, while food security was assessed by comparing rice availability and rice demand. The impacts of land conversion were tested using a Paired Sample t-Test, and projected paddy field decline was estimated through Exponential Triple Smoothing (ETS). The results indicate an increase in built-up land by 31.70 hectares and a decrease in paddy fields by 20.92 hectares between 2018 and 2024, along with reductions in several other land-use classes. Additionally, 7 hectares of Protected Paddy Fields were converted, reflecting weak effectiveness of land-protection policies. Paddy field conversion reduced rice availability from 3,157.35 tons to 2,185.11 tons, while rising demand widened the deficit from –3,835.57 tons to –5,909.94 tons in 2024. The t-Test showed a significant decline in food security, with average fulfillment decreasing from 33.74% to 33.37% (sig. 0.048). ETS projections further indicate that paddy fields will continue to decline and may nearly disappear by 2201–2202 if conversion is not controlled. In conclusion, paddy field conversion poses a substantial threat to Bukittinggi’s food security, and without strict regulation, the region may reach a critical point in the coming years.